Tracing trajectories of audio‐visual learning in the infant brain. Issue 6 (26th October 2016) - Kersey, Alyssa J.; Emberson, Lauren L.
Abstract: Although infants begin learning about their environment before they are born, little is known about how the infant brain changes during learning. Here, we take the initial steps in documenting how the neural responses in the brain change as infants learn to associate audio and visual stimuli. Using functional near‐infrared spectroscopy (fNRIS) to record hemodynamic responses in the infant cortex (temporal, occipital, and frontal cortex), we find that across the infant brain, learning is characterized by an increase in activation followed by a decrease. We take this U‐shaped response as evidence of repetition enhancement during early stages of learning and repetition suppression during later stages, a result that mirrors the Hunter and Ames model of infant visual preference. Furthermore, we find that the neural response to violations of the learned associations can be predicted by the shape of the learning curve in temporal and occipital cortex. These data provide the first look at the shape of the neural response during audio‐visual associative learning in infancy establishing that diverse regions of the infant brain exhibit systematic changes across the time‐course of learning. Abstract : This study takes the initial steps in documenting how the neural responses in the brain change as infants learn to associate audio and visual stimuli. Using functional near‐infrared spectroscopy (fNRIS) to record hemodynamic responses in the infant cortex (temporal, occipital and frontal cortex), we find that across the infant brain, learning is characterized by an increase in activation followed by a decrease. We take this U‐shaped response as evidence of repetition enhancement during early stages of learning and repetition suppression during later stages, a result that mirrors the Hunter and Ames model of infant visual preference.